Assessing insect-based products as feed ingredients for aquaculture - Devic, Emilie Danielle Paule (University of Stirling, 2016)
Research has been actively looking for alternative feed ingredients to reduce the reliance of the aquafeed industry on marine ingredients, namely fish meal (FM) and fish oil (FO). In this context, insects, in particular housefly (Musca domestica) and black soldier fly (BSF, Hermetia illucens) larvae, have been identified as promising candidates. Although a global insect farming industry is emerging, it is for now constrained by regulatory and technical bottlenecks that raise the question ‘where and how insect-based products could be integrated into aquaculture’. The literature indicated a high interspecies variability of the results when replacing FM with insect meals in fish diets and previous work failed to consider the existing challenges related to the insect production to demonstrate commercial relevance and applicability. In this thesis, maggot meals (MM) and frass (insect digestate) were assessed as strategic feed ingredients for two commercially important farmed species: Atlantic salmon, (Salmo salar) and Nile tilapia (Oreochromis niloticus), in their relevant contexts. Case studies showed that both housefly and BSF MM are high quality feed ingredients and suitable alternative to FM. Specifically, dietary inclusions of up to 200 g/kg of crude or defatted housefly larvae meal did not compromised the feed digestibility and utilisation and the growth performance and body composition of salmon parr (freshwater stage), compared to a FM-based control diet. Hormone (17α-methyltestosterone) treated diets containing between 250 and 1000 g/kg BSF or housefly meal were found as effective as a commonly used pure hormone-treated FM in sex-reversal process leading to 99.8 to 100% males, high survival and evenness of the fish produced. In a commercial diet for advanced nursing of Nile tilapia fingerlings, up to 80 g/kg BSF meal was included without impairing the fish performance and body composition; dietary inclusion was limited by the lipid content of the crude MM. Finally, BSF frass derived from brewery spent grains ...